Carbon and Nitrogen Effect on Exopolysaccharides Production of Schizophyllum commune - Syed Ibrahim, Syed Umar; Mohd Nor Rashid, Noraswati; Mel, Maizirwan (2011)
The effects of various carbon and nitrogen sources on the production of mycelial and exopolysaccharides (EPS) by local strain Schizophyllum commune were investigated in shake flask culture. Mycelial growth increased until day 14 whereas EPS peaked at day 11 , and then declined. Dextrin, maltose and soluble starch exhibited good mycelial growth with corresponding mycelial dry weight of 8.26 gIL, 7.27 gIL and 7.13 gIL. EPS productions in dextrin, maltose and soluble starch were 2.4 gIL, 2.4 gIL and 2.3 giL, respectively. From this study, dextrin was found to be the best carbon source to produce the highest mycelial dry weight and EPS. Organic nitrogen sources appeared to be the most appropriate carbon sources for mycelium dry weight and EPS production. Beef extract showed the highest mycelium dry weight (6.5 gIL) whereas yeast extract showed the highest EPS production (2.2 gIL), respectively. Initial pH 6.5 was found to be the optimum for mycelium production (7.4 gIL) and pH 5.5 for EPS production (1.8 gIL ). Therefore, the best carbon and nitrogen sources in liquid culture of S.commune were dextrin and yeast extracts with initial pH 5.5. This medium composition can be used for large scale production process.